2010
DOI: 10.1002/ajp.20896
|View full text |Cite
|
Sign up to set email alerts
|

Kinda baboons (Papio kindae) and grayfoot chacma baboons (P. ursinus griseipes) hybridize in the Kafue river valley, Zambia

Abstract: The ranges of small kinda (Papio kindae) and much larger grayfooted chacma (P. ursinus griseipes) baboons adjoin in the Kafue National Park, Zambia. In a visual survey of baboons at 48 sites in the Kafue River drainage we found that, contrary to previous reports, groups at the species interface near the town of Ngoma are phenotypically diverse and presumably formed by multigenerational hybridization. Mitochondrial and/or Y-chromosome genetic markers from fecal samples (N=164) collected at 29 sites support this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(154 citation statements)
references
References 42 publications
(54 reference statements)
10
144
0
Order By: Relevance
“…These focus on differences in the ecologies of baboons in the national parks at De Hoop [Hill, 1999], Amboseli [Altmann and Alt- These areas of difference primarily affect the chacma baboon range in Botswana and Namibia, and the appropriate parts of each range description are emphasised in italics. The kinda baboon range was described by Jolly et al [2011], the first to recognise its distinctive morphology and genetics, as taking in the extreme SW of Tanzania, Zambia, the S Democratic Republic of the Congo and most of Angola, in keeping with the IUCN maps. mann, 1970;Altmann et al, 1981;Altmann and Muruthi, 1988;Altmann et al, 2002] and Gashaka Gumti [Warren, 2008;Ross et al, 2011;Warren et al, 2011].…”
Section: Species Distributionsmentioning
confidence: 99%
“…These focus on differences in the ecologies of baboons in the national parks at De Hoop [Hill, 1999], Amboseli [Altmann and Alt- These areas of difference primarily affect the chacma baboon range in Botswana and Namibia, and the appropriate parts of each range description are emphasised in italics. The kinda baboon range was described by Jolly et al [2011], the first to recognise its distinctive morphology and genetics, as taking in the extreme SW of Tanzania, Zambia, the S Democratic Republic of the Congo and most of Angola, in keeping with the IUCN maps. mann, 1970;Altmann et al, 1981;Altmann and Muruthi, 1988;Altmann et al, 2002] and Gashaka Gumti [Warren, 2008;Ross et al, 2011;Warren et al, 2011].…”
Section: Species Distributionsmentioning
confidence: 99%
“…Moreover, there is evidence for ancient and ongoing intrageneric hybridization between most species of these genera in areas where their ranges meet [6,12,[56][57][58][59]. Continuing hybridization over generations may lead to the transfer of certain genes into the genome of another species, a process called 'introgression'.…”
mentioning
confidence: 99%
“…In particular, both of these analyses, which sampled widely from the geographical distribution of Papio, found that rather than being a sister lineage, Rungwecebus clustered within the baboon clade. This result indicated that, like other Old World monkeys, such as macaques and indeed many members of the genus Papio (e.g., Stevison and Kohn 2009;Osada et al 2010;Jolly et al 2011), the evolutionary history of the kipunji included episodes of divergence-with-gene-exchange.…”
Section: Rungwecebus Kipunjimentioning
confidence: 89%